Long‐term changes in the migration phenology of UK breeding birds detected by large‐scale citizen science recording schemes. (18th April 2016) - Newson, Stuart E.; Moran, Nick J.; Musgrove, Andy J.; Pearce‐Higgins, James W.; Gillings, Simon; Atkinson, Philip W.; Miller, Ryan; Grantham, Mark J.; Baillie, Stephen R.
Abstract : The timing of migration is one of the key life‐history parameters of migratory birds. It is expected to be under strong selection, to be sensitive to changing environmental conditions and to have implications for population dynamics. However, most phenological studies do not describe arrival and departure phenologies for a species in a way that is robust to potential biases, or that can be clearly related to breeding populations. This hampers our ability to understand more fully how climate change may affect species' migratory strategies, their life histories and ultimately their population dynamics. Using generalized additive models (GAMs) and extensive large‐scale data collected in the UK over a 40‐year period, we present standardized measures of migration phenology for common migratory birds, and examine how the phenology of bird migration has changed in the UK since the 1960s. Arrival dates for 11 of 14 common migrants became significantly earlier, with six species advancing their arrival by more than 10 days. These comprised two species, Blackcap Sylvia atricapilla and Chiffchaff Phylloscopus collybita, which winter closest to Britain in southern Europe and the arid northern zone of Africa, Common Redstart Phoenicurus phoenicurus, which winters in the arid zone, and three hirundines (Sand Martin Riparia riparia, House Martin Delichon urbicum and Barn Swallow Hirundo rustica ), which winter in different parts of Africa. Concurrently, departure dates became significantly later for four of the 14 species and included species that winter in southern Europe (Blackcap and Chiffchaff) and in humid zones of Africa (Garden Warbler Sylvia borin and Whinchat Saxicola rubetra ). Common Swift Apus apus was the exception in departing significantly earlier. The net result of earlier arrival and later departure for most species was that length of stay has become significantly longer for nine of the 14 species. Species that have advanced their timing of arrival showed the most positive trends in abundance, in accordance with previous studies. Related in part to earlier arrival and the relationship above, we also show that species extending their stay in Great Britain have shown the most positive trends. Further applications of our modelling approach will provide opportunities for more robust tests of relationships between phenological change and population dynamics than have been possible previously.